2018
DOI: 10.2174/1874285801812010308
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Intestinal Microbiota in Two Lines of Rainbow Trout (Oncorhynchus Mykiss) Divergently Selected for Muscle Fat Content

Abstract: Background:Recently, studies suggest that gut microbiota contributes to the development of obesity in mammals. In rainbow trout, little is known about the role of intestinal microbiota in host physiology.Objective:The aim of this study was to investigate the link between intestinal microbiota and adiposity, by high-throughput 16S RNA gene based illumina Miseq sequencing in two rainbow trout lines divergently selected for muscle lipid content. Fish from these two lines of rainbow trout are known to have a diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…Earlier studies indicated the dominant phyla in the intestinal microbiota of healthy fish were Proteobacteria and Firmicutes [40,41], this is consistent with the overall results of our study. In addition, Actinobacteria was also found as a dominant phylum in the current study (Figure 2a), which is in accordance with that revealed for rainbow trout (Oncorhynchus mykiss) [42]. Actinobacteria, a phylum of Gram-positive bacteria, is an important secondary metabolite producer and plays a key role in animal intestines [43].…”
Section: Discussionsupporting
confidence: 90%
“…Earlier studies indicated the dominant phyla in the intestinal microbiota of healthy fish were Proteobacteria and Firmicutes [40,41], this is consistent with the overall results of our study. In addition, Actinobacteria was also found as a dominant phylum in the current study (Figure 2a), which is in accordance with that revealed for rainbow trout (Oncorhynchus mykiss) [42]. Actinobacteria, a phylum of Gram-positive bacteria, is an important secondary metabolite producer and plays a key role in animal intestines [43].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it may be worthy to explore the role of Actinobacteria phyla genera members in fish growth, particularly in adult stages, where growth rate is reduced compared with younger life stages for better understating host-gut microbiota interaction in the context of fish growth physiology. Regardless, Actinobacteria is considered a resident of the gut in a variety of fish species, and its relative abundance varies (0% to 50%) between fish species and studies ( Mansfield et al., 2010 ; Desai et al., 2012 ; Gajardo et al., 2016 ; Liu et al., 2016 ; Dehler et al., 2017 ; Ramírez and Romero 2017 ; Betiku et al., 2018 ; Bruce et al., 2018 ; Ricaud et al., 2018 ; Rimoldi et al., 2018 ; Yildirimer and Brown 2018 ; Huyben et al., 2019 ; Serra et al., 2021 ). It has been described that members of the phylum Actinobacteria (i.e., Streptomyces ) are capable of synthesizing diverse bioactive products which can result in benefits to fish health, including antimicrobial activity against pathogens, inducing immune response, tolerance to gut conditions and growth-enhancing effects ( Jami et al., 2015 ; Balagurunathan et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…S3B). After Mycoplasma , Brevinema was the next greatest contributor to similarity in the AFR habitat (>10%) and has previously been isolated from the lower intestines of rainbow trout ( Oncorhynchus mykiss ) (Ricaud et al ., 2018) as well as whitefishes from the Coregonids (Belkova et al ., 2017). Thus, this taxon may be a common colonizer of the salmonid gut, and because Brevinema species have denitrifying capacity (Yang et al ., 2018), they could contribute to nitrogen metabolism in Arctic char.…”
Section: Discussionmentioning
confidence: 99%